Congenital malformations in mice induced by addiction to alcohol and cocaine - Al-Motabagani, MA; Mohamed, AS (East African medical journal, 2005)
To study the teratogenic effect of either alcohol alone, cocaine alone, or a combination of both alcohol and cocaine on mice foetuses. Eighty pregnant mice were divided into four equal groups. In the first (alcohol) group, the pregnant females were given absolute ethanol at 2.5 gm/100 gm twice daily by oro-gastric incubation. In the second (cocaine) group, the pregnant females received cocaine hydrochloride at 20 mg/ 100 gm daily by intraperitoneal injection. In the third (combined) group, the pregnant females received alcohol at 2.5 gm/100 gm twice daily and cocaine hydrochloride at 20 mg/100 gm daily. In all groups the treatment started from the 6th day to the 15th day of gestation. The fourth group is the control. Department of Anatomy, College of Medicine, King Faisal University, Dammam, Saudi Arabia and Department of Anatomy, College of Medicine, Al-Azhar University, Cairo, Egypt. The pregnant mice were sacrificed at the 20th day of gestation (one day before term). The uterine contents were evaluated and the number of dead and live foetuses was determined as well as the number of resorption. The living foetuses were examined for soft tissue anomalies. Eighty pregnant mice. This study revealed a significant increase in the number of dead foetuses and foetal growth parameters showed a significant decrease in the combined group. This group showed significant increase in anomalies of the head as hydrocephaly and complete cleft palate, of the kidney as bilateral secondary hydronephrosis and ectopic kidney, of the limbs, and of the tail as kinked tail. Both alcohol and cocaine groups alone showed significant increase in some of the anomalies of the head while in the alcohol group there was unilateral hydronephrosis. This study indicates that the combined administration of alcohol and cocaine has a more teratogenic effect than either alcohol or cocaine alone.